2021
DOI: 10.3390/biomedicines9030247
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvascular Impairment in COVID-19 Bilateral Pneumonia Assessed by Optical Coherence Tomography Angiography

Abstract: The purpose of this study was to evaluate the presence of retinal and microvascular alterations in COVID-19 patients with bilateral pneumonia due to SARS-COV-2 that required hospital admission and compare this with a cohort of age- and sex-matched controls. COVID-19 bilateral pneumonia patients underwent retinal imaging 14 days after hospital discharge with structural optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) measurements. Vessel density (VD) and foveal avascular zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
78
4
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 44 publications
12
78
4
5
Order By: Relevance
“…In our previous cross-sectional case–control research project, we found a decrease in the macular vascular density of the recovered COVID-19 patients [ 12 ]. Other later reports also support these optical coherence tomography angiography (OCTA) findings of COVID-19 patients [ 13 – 16 ].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In our previous cross-sectional case–control research project, we found a decrease in the macular vascular density of the recovered COVID-19 patients [ 12 ]. Other later reports also support these optical coherence tomography angiography (OCTA) findings of COVID-19 patients [ 13 – 16 ].…”
Section: Introductionmentioning
confidence: 54%
“…The findings of the present study are in line with those of the previous research performed on the retinal microvascular changes in patients with COVID-19. In recent case–control studies, using Optovue AngioVue OCTA machine, alterations of retinal microvasculature are found subsequent to COVID-19 infections, compared to healthy control groups [ 12 , 13 ]. Moreover, in a case–control study performed on patients with mild, moderate, and severe COVID-19 and normal controls, patients with moderate and severe disease had decreased macular VD on OCTA, compared to control subjects or even those who were asymptomatic or paucisymptomatic [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among cases-control studies and case series, 18 publications (10 case-control studies [17][18][19][20][21][22][23][24][25]30 and 9 case series 13,28,29,[31][32][33][34][35][36] ) reported on the presence or absence of retinal signs related to micro-vasculopathy. Among the 10 case-control studies, retinal signs were reported in 6, with frequency ranging from 0.01% to 20%.…”
Section: Summary Findings Of Retinal Features Related To Micro-vasculopathymentioning
confidence: 99%
“…However, since the initial report by Marinho, several case-control studies have reported retinal features in patients with COVID-19 infection of various severity. [17][18][19][20][21][22][23][24][25] In addition to clinical features, several OCT angiography (OCTA) studies demonstrated reduction in vessel density (VD) in COVID patients, which corroborated with the possibility of COVID-19 related retinal micro-vasculopathy. [17][18][19][20][23][24][25][26] Importantly, these perfusion deficits have been detected in asymptomatic individuals with no significant medical comorbidities who have recovered from seemingly mild COVID infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation